Analysis of Operational Heat Exchanger Network Robustness via Interval Arithmetic - Floquet, P.; Hétreux, Gilles; Hétreux, Raphaele; Payet, Lucille (Computer Aided Chemical Engineering, 2016)
This work is part of the RREFlex project whose general objective is the development of robust software dedicated to the synthesis of flexible heat exchanger networks. This paper presents a methodology for analyzing the robustness of a Heat Exchanger Network (HEN) subject to fluctuations of process parameters (inlet temperature, heat transfer coefficient, etc.). It helps operational staff to locate sensitive streams and quantify the impact of these disturbances on the performance of the entire system. Based on a linear system and interval arithmetic, the computational effort is minimal and it allows the study of a great number of scenarios.